DOI: 10.11606/d.25.2013.tde-14082013-101851
|View full text |Cite
|
Sign up to set email alerts
|

Aconselhamento informativo para adultos e idosos usuários de aparelho de amplificação sonora individual: avaliação da eficácia de um material online

Abstract: Wilcoxon) da pontuação total e de algumas tarefas individuais do PHAST entre os intervalos 2 e 3. Não houve diferença das pontuações entre os grupos. Os participantes atribuíram pontuações acima de oito (escala de 0 a 10) quanto ao auxílio fornecido pelos materiais informativos na compreensão das informações quanto ao uso e cuidados com o AASI. Maior pontuação foi obtida para o material online quanto ao conteúdo "manipulação do controle de volume". Cerca de 80% dos participantes do estudo relataram que gostari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…At first, it is important to mention there was great diversity of handling skills with hearing aid devices, both among experienced (PHAST score ranging from 32 to 100%) and for new users (ranging from 29 to 100%). A study observed PHAST scores for new hearing aid users ranging from 60 to 100% (16) . Other studies with experienced hearing aid users observed changes in the total PHAST score, between 48.0 and 100.0% (5) and 61.2 and 100.0% (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At first, it is important to mention there was great diversity of handling skills with hearing aid devices, both among experienced (PHAST score ranging from 32 to 100%) and for new users (ranging from 29 to 100%). A study observed PHAST scores for new hearing aid users ranging from 60 to 100% (16) . Other studies with experienced hearing aid users observed changes in the total PHAST score, between 48.0 and 100.0% (5) and 61.2 and 100.0% (9) .…”
Section: Discussionmentioning
confidence: 99%
“…No correlations between age and handling skills were observed. Literature showed poor significant negative correlations between age and PHAST results (5,16) , and such results were partly attributed to work memory deficits and manual skills, related to age. In this study, these relationships may not have been observed because the participants were mostly elderly, and 60% of them were above 70 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, this population presents more difficulty in understanding the information because of declining age, which, most often, makes this process slower and more complex. In this context, it is important to mention the time spent, the language used and the age of the individual are some of the aspects that will interfere with the retention of the information transmitted (4) . Therefore, to carry out a follow-up of individuals who acquired HA through SUS and serve them in all their needs becomes a hard task, considering the geographic size of Brazil and its people and, mainly, the heterogeneity in the distribution of health professionals, including speech language pathologists (5) .…”
Section: Introductionmentioning
confidence: 99%
“…It is an additional opportunity the patient has to have access, as many times as necessary, to the information given in the appointment with the speech-language pathologist. The way such information is presented is essential not only for the assimilation but also for the understanding of the individual (4,7,8) . This strategy shows to be important because the time spent to provide the information and the guidance about the use, cares and manipulation of the HA is 42 minutes (9) ; this time can be smaller, about 15 and 20 minutes (10) .…”
Section: Introductionmentioning
confidence: 99%